The Implementation of Liability Accounting on Managerial Performance in PT. Telkom Tbk, Medan Branch - Yuni Syahputri; Teddi Pribadi; Hasbiana Dalimunthe (Budapest International Research and Critics University, 2020)
This study aims to examine the effect of the application of responsibility accounting on managerial performance. The sample used in this study were 35 respondents. Data obtained by purposive sampling method. Data collection was carried out using a questionnaire. A total of 35 questionnaires were sent and 35 questionnaires were returned. The research hypothesis was tested using a simple regression method with the help of SPSS (Statistical Product and Service Solutions). Based on the results of this study, it can be concluded that the application of responsibility accounting has a significant effect on managerial performance.